Karbon Aktif Tersulfonasi dari Sekam Padi sebagai Katalis Asam Padat pada Sintesis Biodiesel dari PAO (Palm Acid Oil) - Haryono, (ReTII, 2024)
The scarcity of fossil fuels as a result of excessive use is a serious problem in the energy sector, so renewable and environmentally friendly alternative fuels are needed, one of which is biodiesel. Biodiesel can be obtained through an esterification or transesterification process with free fatty acids or triglycerides as raw materials with short chain alcohols catalyzed by acids or bases. The aim of this research is to synthesize sulfonated activated carbon from rice husks as a solid acid heterogeneous catalyst for the synthesis of biodiesel from palm acid oil (PAO). The sulfonated activated carbon catalyst is prepared from rice husk charcoal which is activated with a mixture of carbonate salts, then the activated carbon is acidified through impregnation of sulfonic functional groups from sulfuric acid with the help of a microwave. The performance test of the solid acid catalyst for biodiesel synthesis was carried out at a PAO to methanol mole ratio of 1:32 and a catalyst content of 3%. The biodiesel synthesis reaction was carried out at 65Â°C for 2 hours. The research results showed that the sulfonate functional group (-SOâ‚ƒH) was identified from the FTIR results of absorption at the wave number 1216 cm-1. These results confirm that the acidification of activated carbon from rice husks has been successfully carried out. The acid density test on the catalyst obtained an acidity value of 3.21 mmol H+/g. In the performance test of the solid acid catalyst for biodiesel synthesis, biodiesel was obtained with a yield of 88.4%, and 83.74% of free fatty acids from PAO were successfully converted into biodiesel.